Feline T-Cell Receptor 𝛾 V- and J-Region Sequences Retrieved from the Trace Archive and from Transcriptome Analysis of Cats - Alexander Thomas Andreas Weiss; Werner Hecht; Manfred Reinacher (Veterinary Medicine International)
The variable domains of antigen receptors are very diverse and assembled in a modular system from a number of V-, D-, and J-region genes. Here we describe additional variants of V- and J-region genes of the feline T-cell receptor 𝛾 (TRG) as well as the corresponding RSSs retrieved from Trace Archive of feline genomic sequences. Additionally, an unusually recombined TRGV-domain containing a partial inverted repeat of the included J-region and a short interspersed element of the CAN-SINE family located within the feline T-cell receptor 𝛾 locus are also described.